2021
DOI: 10.2214/ajr.19.22498
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Radiologic Predictors of Parastomal Hernia Development After End Colostomy

Abstract: Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 17 publications
2
8
0
Order By: Relevance
“…We also found that PSH was significantly increased in patients with diabetes mellitus (HR 1.81) and COPD (HR 1.78). Although colorectal studies have disclosed this association [16,17], to our knowledge, this is the first study in the field of urology that validates the predisposing role of these two factors. Diabetes and COPD may increase the risk of PSH through collagen synthesis impairment and chronic increase in intra‐abdominal pressure, respectively.…”
Section: Discussionmentioning
confidence: 76%
“…We also found that PSH was significantly increased in patients with diabetes mellitus (HR 1.81) and COPD (HR 1.78). Although colorectal studies have disclosed this association [16,17], to our knowledge, this is the first study in the field of urology that validates the predisposing role of these two factors. Diabetes and COPD may increase the risk of PSH through collagen synthesis impairment and chronic increase in intra‐abdominal pressure, respectively.…”
Section: Discussionmentioning
confidence: 76%
“…This may be because women have significantly thinner muscles and thicker subcutaneous fat than men, regardless of their age 37 . A study of radiologic predictors of PSH development after end colostomy found that abdominal adipose tissue volume ratio and total muscle mass density were significantly associated with the occurrence of PSH 38 . This physiological difference may make female patients more prone to developing PSH.…”
Section: Discussionmentioning
confidence: 99%
“…37 A study of radiologic predictors of PSH development after end colostomy found that abdominal adipose tissue volume ratio and total muscle mass density were significantly associated with the occurrence of PSH. 38 This physiological difference may make female patients more prone to developing PSH. At the same time, studies have found that most women increase their abdominal subcutaneous fat by more than 20% after menopause.…”
Section: Discussionmentioning
confidence: 99%
“…These hernias are considered different from mucosal prolapse or a Siphon loop, considered a subcutaneous folding of the exceeding bowel length at the stoma [22]. According to Pennings and coworkers [23], chronic obstructive pulmonary disease, longer operation time, and larger abdominal wall defects at the colostomy site (> 34 mm) can predict the development of parastomal hernias.…”
Section: Parastomal Wall Herniasmentioning
confidence: 99%